The Effect of Health Education Toward Preventive Measures Of COVID-19 Among Employees in Duhok City-Iraq: A Cluster Randomized Controlled Trial - Ibrahim, Waleed Khalid; Abdulrahman, Masood Abdulkareem (International Journal of Membrane Science and Technology, 2023)
Background: Increasing the knowledge, attitudes, and behaviours of public sector employees regarding COVID-19 is one of the most effective ways to stop the spread of this virus. A substantial portion of the community is made up of people who work in the public sector. The purpose of this study is to evaluate and enhance government workers’ knowledge, attitude, and practice (KAP) regarding COVID-19 preventive measures among directorates in Duhok city in Iraqi Kurdistan. Methods: A cluster randomized controlled trial was conducted among directorates’ employees in Duhok city, the age ranged between 18 and 75. Simple random sampling was used in the study. A structured questionnaire was applied for pre and post-test for intervention and control group. The KAP questions included COVID-19 preventive measures (vaccines, face masks, social distances and hygiene). Results: The findings demonstrated that intervention group improved significantly at (P<0.01) toward KAP related to COVID-19 preventive measures. In terms of knowledge, attitude, and practice of COVID-19 preventive measures, the intervention group exceeded the control group on the post-test compared to the pre-test. The significant changes were recorded among good level of economic status by (2.69) degrees increased in the difference between pre and post-test in intervention group. In contrast, there are no improving in the post-test among those very low income in terms of knowledge at (P<0.01). however, the second large improvement was related to practice from (5.05) increased to (6.61) at (P<0.01). All other demographic characteristics, including age, occupation, religion, education, and place of residence, showed statistically significant variance at (P <0.01). Conclusion: Health education is regarded as beneficial for general awareness and crucial COVID-19 preventive measures.